Contamination of Bacillus cereus in Elementary School Snack Food - Ayu fahani; Ratih Dewi Dwiyanti; Ahmad Muhlisin (Tropical Health and Medical Research, 2019)
Many food snacks have the advantage but still have health risks as evidenced by the many cases of food poisoning, one of the causes of food poisoning is Bacillus cereus. This study aims to determine the amount and percentage of Bacillus cereus pollution on snacks sold in elementary schools. This research is expected to provide information to the public about the presence or absence of bacteria Bacillus cereus contamination. This research uses purposive sampling technique. The sample used in this study was hawker food sold in Elementary School as many as 20 samples consisting of 10 samples that have not fried and ten samples that have cooked. The results of the questionnaire study showed 83% of sellers did not put snacks in closed containers and found Bacillus cereus in meals. Conclusion 9 (45%) of food samples contaminated with Bacillus cereus bacteria